2014
DOI: 10.1371/journal.pone.0097224
|View full text |Cite
|
Sign up to set email alerts
|

White-Nose Syndrome Fungus: A Generalist Pathogen of Hibernating Bats

Abstract: Host traits and phylogeny can determine infection risk by driving pathogen transmission and its ability to infect new hosts. Predicting such risks is critical when designing disease mitigation strategies, and especially as regards wildlife, where intensive management is often advocated or prevented by economic and/or practical reasons. We investigated Pseudogymnoascus [Geomyces] destructans infection, the cause of white-nose syndrome (WNS), in relation to chiropteran ecology, behaviour and phylogenetics. While… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
74
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(88 citation statements)
references
References 43 publications
8
74
0
1
Order By: Relevance
“…Infection involves deep penetration of the subcutaneous tissue by fungal hyphae, causing ulcerative necrosis and tissue destruction (7,(9)(10)(11). P. destructans typically forms more superficial infections in European bat populations, with no evidence for associated mortality (9,12), although a recent study also found evidence of invasive WNS lesions in European bats (13). Current models suggest that P. destructans is an invasive species that originated in Europe, where native bat species may be more resistant to the most debilitating forms of the disease (9).…”
mentioning
confidence: 99%
“…Infection involves deep penetration of the subcutaneous tissue by fungal hyphae, causing ulcerative necrosis and tissue destruction (7,(9)(10)(11). P. destructans typically forms more superficial infections in European bat populations, with no evidence for associated mortality (9,12), although a recent study also found evidence of invasive WNS lesions in European bats (13). Current models suggest that P. destructans is an invasive species that originated in Europe, where native bat species may be more resistant to the most debilitating forms of the disease (9).…”
mentioning
confidence: 99%
“…It has now been confirmed in at least 14 European countries and is suspected in four more due to convincing photographic evidence (Frick and others, 2014) from 18 bat species (Martínková and others 2010, Wibbelt and others 2010, Puechmaille and others 2011, Zukal and others 2014). However, there has been no known incidence of mass mortality of bats due to P. destructans in Continental Europe (Puechmaille and others 2011).…”
mentioning
confidence: 86%
“…mystacinus, M. blythii, M. daubentonii, M. brandtii, M. emarginatus, M. nattereri, M. bechsteinii and M. escalerai/sp. A. The list of species with P. destructans infection is likely to increase as sampling intensity increases as illustrated by the recent Zukal et al (2014) study which reported infection of a few individuals from three more species of the family Vespertilionidae, Eptesicus nilssonii, Plecotus auritus and Barbastella Barbastellus, as well as on a single individual of Rhinolophus hipposideros, of the family Rhinolophidae.…”
Section: Status Of P Destructans/wns In Europementioning
confidence: 99%
“…In Europe, P. destructans invasion of the wing membrane is generally restricted to the epidermis and adnexae without deep invasion into the underlying connective tissue but with occasional formation of neutrophilic pustules, contrasting with the common and extensive invasion of dermal connective tissue in bats from North America (Pikula et al 2012;Wibbelt et al 2013;Zukal et al 2014;Bandouchova et al 2015). Based on investigation of two euthanized individuals, P. destructans invasion in the skin of the muzzle seems to be more pronounced than invasion of the wing membrane (Pikula et al 2012;Wibbelt et al 2013).…”
Section: Status Of P Destructans/wns In Europementioning
confidence: 99%
See 1 more Smart Citation